Pengaruh Strategi Bisnis dan Marketing terhadap Keputusan Pembelian dengan Digital Marketing sebagai Variabel Interveing (Studi Kasus pada PT Summarecon Agung, Tbk.) - Adelina Prabella; Aty Herawati (Syntax Idea)
This study aims to determine the effect of Business and Marketing Strategy on Purchasing Decisions at PT Summarecon Agung, Tbk. Mediated by Digital Marketing. The research population is consumers who have purchased property and real estate at PT Summarecon Agung, Tbk. A sample of 100 people is taken by convenience sampling. The primary data used is in the form of consumer responses from PT Summarecon Agung, Tbk., regarding business and marketing strategies for purchasing decisions mediated by digital marketing obtained through distributing questionnaires. Data were analyzed using PLS-based SEM. The results of the study show that Business Strategy and Marketing has an effect on Digital Marketing, Business Strategy and Marketing has a direct effect on Purchasing Decisions. And Business Strategy and Marketing indirectly influence Purchasing Decisions mediated by Digital Marketing.